2013
DOI: 10.4103/2277-9175.109742
|View full text |Cite
|
Sign up to set email alerts
|

Clear cell hidradenoma

Abstract: Clear cell hidradenoma or nodulocystic hidradenoma or acrospiroma are histologically distinct relatively rare tumors of sweat gland duct origin, found mainly in adults with a female preponderance. We report a case of eccrine hidradenoma in a 31-year-old man who presented with an asymptomatic, solitary nodule on occipital region. A few reports are available in literature regarding presence of this tumor on occipital region of young man and present case is being reported because of its rarity in this region of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…[4]. • A few reports are available in literature regarding presence of this tumour on occipital region [3]. It typically presents as a painless nodule, consistent with our case.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…[4]. • A few reports are available in literature regarding presence of this tumour on occipital region [3]. It typically presents as a painless nodule, consistent with our case.…”
Section: Discussionsupporting
confidence: 86%
“…• Clear cell hidradenoma or nodulocystic hidradenoma or acrospiroma are histologically distinct relatively rare tumours of sweat gland duct origin, found mainly in adults with a female preponderance [3]. • It affects all ages, most commonly females in fourth to eighth decades of life.…”
Section: Discussionmentioning
confidence: 99%
“…CCH may be asymptomatic or may present with pain, or bleeding, and rarely can show malignant transformation [10]. Ulcerated lesions may resemble squamous cell carcinoma, basal cell carcinoma metastatic disease or other adnexal tumors [11][12][13]. Dermoscopy shows a nodule of amorphous, white-pink areas, red lacuna-like areas, eccentric ulceration, as well as hairpin, dotted, and linear irregular vessels [14].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this study showed that 89% of cancer cells in colorectal tumors that metastasize to lymph nodes express EPCAM, and 10% express it less. 124…”
Section: Epithelial Cellular Adhesion Molecule (Epcam)mentioning
confidence: 99%